Anaphylaxis to Pfizer/BioNTech mRNA COVID-19 Vaccine in a Patient With Clinically Confirmed PEG Allergy - McSweeney, Morgan D.; Mohan, Manoj; Commins, Scott P.; Lai, Samuel K. (Frontiers in Allergy, 2021)
Although allergic responses to the mRNA COVID-19 vaccines are rare, recent reports have suggested that a small number of individuals with allergy to polyethylene glycol (PEG), a component of the mRNA lipid nanoshell, may be at increased risk of anaphylaxis following vaccination. In this report, we describe a case of a patient who received an mRNA COVID-19 vaccine, experienced anaphylaxis, and was subsequently confirmed to have anti-PEG allergy by skin prick testing. The patient had previously noticed urticaria after handling PEG powder for their occupation and had a history of severe allergic response to multiple other allergens. Importantly, as many as 70% of people possess detectable levels of anti-PEG antibodies, indicating that the detection of such antibodies does not imply high risk for an anaphylactic response to vaccination. However, in people with pre-existing anti-PEG antibodies, the administration of PEGylated liposomes may induce higher levels of antibodies, which may cause accelerated clearance of other PEGylated therapeutics a patient may be receiving. It is important to improve awareness of PEG allergy among patients and clinicians.